Identifying Students’ Misconceptions about Chemical Bonding Using a Four-Tier Diagnostic Test - Agung, Darius; Muhab, Sukro; Irwanto, Irwanto (Journal of Research in Education and Pedagogy, 2024)
Chemical bonding is an abstract topic that students rarely encounter in their daily lives. Because of the many misconceptions that can arise regarding chemical bonds, it is not surprising that chemical bonds are a topic that has been widely researched. Thus, this study aims to explore students’ understanding of chemical bonding. This research is quantitative research using a survey design. The participants were 101 tenth-grade students at a public high school in Indonesia. In this study, the sample was determined using convenience sampling techniques. To collect the required data, the Four-Tier Diagnostic Test for Chemical Bonding (FTDT-CB) was administered. The results indicated that students’ understanding of chemical bonding concepts was relatively low with an average score of 18 (out of 100). In addition, 23 misconceptions were identified, of which 20 were genuine misconceptions while the other 3 were spurious misconceptions. It is recommended for future studies to conduct quasi-experimental research to prevent misconceptions that emerged in the current research and also to reveal misconceptions on chemical bonding that may be experienced by pre-service chemistry teachers by using a four-tier diagnostic test.